2006
DOI: 10.1093/esr/jcl001
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Labour Market Outcomes: The Non-Monetary Benefits of Social Capital

Abstract: . Getting a Job: A Study of Contacts and Careers. University of Chicago Press) that social networks help individuals to find better-paid jobs with a new model, which predicts that networks are helpful with respect to non-pecuniary job characteristics but not concerning the monetary pay-offs. Following Montgomery (Montgomery, J. D. (1992) American Sociological Review, 57, 586-596), our model is a combination of classical job-search theory and the network hypothesis. First, concerning the monetary consequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
1
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(143 citation statements)
references
References 28 publications
4
116
1
15
Order By: Relevance
“…Their results reveal a lower probability of over-education when the job was found through formal channels (e.g., job advertisements), while personal contacts appear to increase the probability of over-education. However, Franzen and Hangartner (2006) get the opposite results. Using 2001 Swiss data they show that social networks and direct job application procedures lead to higher status occupations compared to formal channels.…”
Section: Social Capital and The Labour Marketmentioning
confidence: 90%
“…Their results reveal a lower probability of over-education when the job was found through formal channels (e.g., job advertisements), while personal contacts appear to increase the probability of over-education. However, Franzen and Hangartner (2006) get the opposite results. Using 2001 Swiss data they show that social networks and direct job application procedures lead to higher status occupations compared to formal channels.…”
Section: Social Capital and The Labour Marketmentioning
confidence: 90%
“…An enormous body of research literature can be found at the individual level which, for instance, analyses how social capital improves employment situations (Franzen, Hangartner 2006, Granovetter 1995, Mouw 2003, Obukhova, Lan 2013, Thompson 2005 or related economic outcomes (Boxman et al 1991, Gerber, Mayorova 2010, Kwon et al 2013, Lancee 2010. Furthermore, Lee (2009) stated for the meso-level that "social capital is potentially an important source of competitive advantage for all organisations" (Cooke et al 2005, see Tsai, Ghoshal 1998 of these studies (Rupasingha et al 2000, Westlund, Calidoni-Lundberg 2007 analysed subnational regions in one country and the organisational density as a measure of social capital in a way that is congruent with this paper's approach (see section 3).…”
Section: Empirical Studies On Social Capital and Economic Well-beingmentioning
confidence: 99%
“…If for an employed person, its current JS falls below the minimum level, which is the same for all persons 5 , it starts onthe-job search. In contrast with the unemployed, who consider all matching vacancies, the employed consider only those matching vacancies with the expected JS being higher than their current JS.…”
Section: A Job Searchmentioning
confidence: 99%
“…Studies show that between 30 and 50 per cent of individuals found their new jobs through friends and relatives [5], [6], and individuals with access to larger social networks use informal job search channels more often [7]. Moreover, social support from co-workers and managers, along with other factors, is an important component of job satisfaction [8]- [12].…”
Section: Introductionmentioning
confidence: 99%